Дисциплина обслуживания в мультисервисных сетях, минимизирующая максимальную задержку пакетов - Пустовойтов, П. Е.; Раскин, Л. Г. (ХНУРЕ, 2013)
For the telecommunication network node it was proposed a method for solving the task of the packets aggregation transfer order optimization with the well-known dynamics of network elements busy period. To solve the problem it was suggested the criterion - maximum duration of packet delivery, which is minimized. The current problem reduces to solving a set of two-indexed assignment problems. It was done the estimation of expediency assessment for packet transfer order optimization method usage. The gain, obtained using packet transfer order optimization, increases with the increasing of number of transferred packets and increasing the variability of queue length of awaiting service packets in intermediate nodes. It was suggested equations for variability level estimation. Using the simulation model, it was constructed graphs, which show the gain of packet transfer optimization procedure for the different packet number in queue.
Keywords: задержка пакета